2015
DOI: 10.1017/s1368980015002955
|View full text |Cite
|
Sign up to set email alerts
|

Child-care nutrition environments: results from a survey of policy and practice in New Zealand early childhood education services

Abstract: Objective: To describe nutrition environments in formal child care for 3-and 4-year-olds. Design: Cross-sectional online survey of nutrition-related child-care policy and practice. Written nutrition policies were analysed using the Wellness Child Care Assessment Tool. Setting: Licensed child-care services in the Auckland, Counties Manukau and Waikato regions of New Zealand. Subjects: Eight hundred and forty-seven services (private and community day care, kindergartens and playcentres). Results: Managers/head t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 29 publications
4
51
0
Order By: Relevance
“…A small number of services bought the food from a local corner store, takeaway/fast‐food shop or bakery (n=5; 3.4%) or a local fruit and vegetable grocer (n=9; 6.2%). Food provided by services on special occasions has been reported in an earlier paper 31 …”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…A small number of services bought the food from a local corner store, takeaway/fast‐food shop or bakery (n=5; 3.4%) or a local fruit and vegetable grocer (n=9; 6.2%). Food provided by services on special occasions has been reported in an earlier paper 31 …”
Section: Resultsmentioning
confidence: 94%
“…The current study aimed to describe the provision, source and cost of daily food provision to 3‐ and 4‐year‐old children in licensed ECE services; compare weekly menus to guidelines regarding the number of serves from the four main food groups, variety within the four food groups, and the limiting of foods classified as ‘sometimes’ or ‘occasional’; and determine if compliance with the guidelines was associated with ECE service characteristics and/or cost of menu. Previous research on nutrition policy and food‐related behaviours in NZ early education settings found statistically significant differences by type of service (privately‐owned compared with community‐based daycare, kindergartens and playcentres) and little or no difference by neighbourhood deprivation 31 . This paper explores if these findings hold for the food provided in early education settings.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…It is also recommended by INFORMAS to include early child care and/or education settings. These settings have been studied previously in NZ and were therefore not included as part of this national study and the resulting country profile.…”
Section: Methodsmentioning
confidence: 99%